2015
DOI: 10.1530/erc-15-0109
|View full text |Cite
|
Sign up to set email alerts
|

The role of proto-oncogene GLI1 in pituitary adenoma formation and cell survival regulation

Abstract: The Hedgehog (Hh) pathway is an important regulator of early tissue patterning and stem cell propagation. It was found to be aberrantly activated in numerous types of human cancer and might be relevant in cancer stem cells. The identification of adult stem cells in the pituitary raised the question if tumor-initiating cells and Hh signaling are involved in pituitary adenoma formation. The present study aimed at the evaluation of Hh signaling in relation to stem cell and cell cycle markers in 30 human pituitary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
(41 reference statements)
1
13
0
Order By: Relevance
“…As mentioned previously, transgenically induced ACP showed increased production of SHH by the β-catenin-activated SOX2 + cells, which then may contribute to ACP development and tumor cell proliferation (Andoniadou et al 2012(Andoniadou et al , 2013. Some SHH-associated genes were also found upregulated in the SP of human pituitary tumors when compared to the bulk non-SP (Mertens et al 2015) (Table 1), and GLI1 expression seems to go together with SOX2 expression as analyzed in a cohort of pituitary adenomas (Lampichler et al 2015).…”
Section: Dysregulation Of Shh In Pituitary Tumorigenesismentioning
confidence: 52%
“…As mentioned previously, transgenically induced ACP showed increased production of SHH by the β-catenin-activated SOX2 + cells, which then may contribute to ACP development and tumor cell proliferation (Andoniadou et al 2012(Andoniadou et al , 2013. Some SHH-associated genes were also found upregulated in the SP of human pituitary tumors when compared to the bulk non-SP (Mertens et al 2015) (Table 1), and GLI1 expression seems to go together with SOX2 expression as analyzed in a cohort of pituitary adenomas (Lampichler et al 2015).…”
Section: Dysregulation Of Shh In Pituitary Tumorigenesismentioning
confidence: 52%
“…Therefore, the understanding of pituitary adenoma occurrence/progression and the acquirement of invasiveness is of critical importance for both diagnosis and treatment. One study showed that the occurrence and progression of pituitary adenoma might be related with the absence of tumor suppressor gene or expression of oncogenes [27]. MicroRNA is a biological marker for human tumors, and has important roles in the biological process of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Our present data is similar to the previous studies, and showed the activation of Gli1 expression in glioma tissue as well as in two glioma cell lines (U251 and U87) by qRT-PCR and western blotting analysis. Although a comprehensive analysis of direct transcriptional targets of Gli1 at the genomic level is lacking, a number of studies have shown that Gli1 directly regulates the transcription of various genes that are known to be involved in cell proliferation, survival, and chemotolerance (16 - 18) .…”
Section: Discussionmentioning
confidence: 99%